Recent Perspectives on Corneal Nerves: A Short Review - Joy Sarkar, PhD (The Ophthalmology, 2017)
This mini-review provides an overview of recent trends in our understanding of the general structure of the cornea, the importance of corneal nerves, their function and distribution in the different layers of the cornea based on reports obtained by imaging techniques such as in vivo confocal microscopy (IVCM) and immunohistochemistry (IHC) analysis. Recent data on corneal nerve status in conditions such as Dry Eye Disease (DED) and Diabetes is also discussed. There is additional emphasis on corneal nerve damage due to injury especially during surgical interventions and underlying disease states as well as translational research on corneal nerve regeneration. Information on recent clinical studies on the effect of laser corneal surgery and its impact on corneal nerves is also presented.